Regulatory T Cells Increase After rh-MOG Stimulation in Non-Relapsing but Decrease in Relapsing MOG Antibody-Associated Disease at Onset in Children - Horellou, Philippe; de Chalus, Aliénor; Giorgi, Laetitia; Leroy, Carole; Chrétien, Pascale; Hacein-Bey-Abina, Salima; Bourgeois, Christine; Mariette, Xavier; Serguera, Ché; Le Grand, Roger; Deiva, Kumaran (Frontiers in Immunology, 2021)
Background: Myelin oligodendrocytes glycoprotein (MOG) antibody-associated disease (MOGAD) represent 25% of pediatric acquired demyelinating syndrome (ADS); 40% of them may relapse, mimicking multiple sclerosis (MS), a recurrent and neurodegenerative ADS, which is MOG-Abs negative. Aims: To identify MOG antigenic immunological response differences between MOGAD, MS and control patients, and between relapsing versus non-relapsing subgroups of MOGAD. Methods: Three groups of patients were selected: MOGAD (n=12 among which 5 relapsing (MOGR) and 7 non-relapsing (MOGNR)), MS (n=10) and control patients (n=7). Peripheral blood mononuclear cells (PBMC) collected at the time of the first demyelinating event were cultured for 48 h with recombinant human (rh)-MOG protein (10 g/ml) for a specific stimulation or without stimulation as a negative control. The T cells immunophenotypes were analyzed by flow cytometry. CD4+ T cells, T helper (Th) cells including Th1, Th2, and Th17 were analyzed by intracellular staining of cytokines. Regulatory T cells (Tregs, Foxp3+), CD45RA-Foxp3+ Tregs and subpopulation naive Tregs (CD45RA+Foxp3int), effector Tregs (CD45RA-Foxp3high) and non-suppressive Tregs (CD45RA-Foxp3int) proportions were determined. Results: When comparing unstimulated to rh-MOG stimulated T cells, a significant increase in the proportion of Th2 and Th17 cells was observed in MOGAD. Increase of Th17 cells was significant in MOGNR but not in MOGR. CD4+ Tregs were significantly increased in MOGNR while they decreased in MOGR. CD45RA-Foxp3+ Tregs were significantly decreased in MOGR, but not in MOGNR. MOGR showed the highest ratio of effector Tregs/non suppressive-Tregs, which was significantly higher than in MOGNR. Conclusions: Our findings suggest that CD4+ Th2 and Th17 cells are involved in the pathophysiology of MOGAD in children. The opposite response of Tregs to rh-MOG in MOGNR, where CD4+ Tregs increased, and in MOGR, where CD45RA-Foxp3+ Tregs decreased, suggests a probable loss of tolerance toward MOG autoantigen in MOGR which may explain relapses in this recurrent pediatric autoimmune disease.